PERSPEKTIF MASYARAKAT KAMPUNG BEDAGAI TERHADAP MUHAMMADIYAH DI KELURAHAN KOTAPINANG KECAMATAN KOTAPINANG KABUPATEN LABUHAN BATU SELATAN - Nasution, Siti Sulaiha; siregar, rosmaimunah; Lubis, Jumaita Nopriani; Wahyuni, Sri (Tarim : Jurnal Islamic Eduation, 2023)
This research is motivated by the existence of different perspectives in the community of Bedagai Village, people are not yet familiar with Muhammadiyah and there are still many people who do not understand about Muhammadiyah, especially in the general public. Thepurpose of this research is to find out the community's perspective on Muhammadiyah. This research is qualitative research. Data collection techniques use observation, interviews and documentation. The data is analyzed using data reduction, data presentation and inference.The results of this study are The perspective of the people of Bedagai Village towards Muhammadiyah is very diverse, some are supportive, some feel ordinary, but not a few also welcome the return of Muhammadiyah in the region. The community feels that there is a great benefit for the community such as in terms of providing places of worship, spiritual guidance such as recitation, social activities, and education starting from early childhood to elementary school. With the acceptance and enthusiasm of the local community, it can be concluded that the Muhammadiyah movement in this region can develop considering the full support and openness of the community about the Muhammadiyah Organization so that Muhammadiyah da'wah can take place well.